(untitled) (Analysis in Theory and Applications, 2014)
Let L=-Δ+V be the Schrödinger operator on R^d, where Δ is the Laplacian on R^d and V e0 is a nonnegative function satisfying the reverse Hölder's inequality. The authors prove that Riesz potential J_β and its commutator [b,J_β] associated with L map from M_α,v^p,q into M_α,v^p_1,q_1.